Investigation on serum calcium (Ca), phosphorus (P) and alkaline phosphatase (AP) levels in cows with retained placenta - Akar, Y; Yildiz, H; Keçeci, H; Aydin, M (Scientific Technical Research Council Turkey, 2002)
In this study. calcium (Ca), phosphorus (P) and alkaline phosphatase (AP) levels of the blood serum of cows with retained placenta (RP) were measured and the role of these parameters on the etiology of the RP was investigated. A total of 28 different ages and breeds of cows, of which 14 (group I) had retained placenta and 14 (group 2) discharged fetal membranes (within 3-8 hours of delivery) were used as the material of the study. Additionally, these two groups were divided into two subgroups, according to the sexes of their calves, and three subgroups called groups A (3 years). B (4-6 years) and C (greater than or equal to7 years), according to their ages. Their serum levels of Ca, P and AP levels were determined by spectrophotometry. The serum levels of Ca, P and AP were found to be respectively 7.93+/-0.38 mg/dl, 6.02+/-0.52 mg/dl and 14.29+/-0.97 IU/L in group 1 and 8.51+/-0.39 mg/dl. 6.18+/-0.50 mg/dl and 17.15+/-1.62 IU/L in group 2, with no difference between the groups (Pgreater than or equal to0.05). When the serum levels of Ca, P and AP were evaluated in terms of sex, the difference between the groups was found to be nonsignificant (Pgreater than or equal to0.05). However, when the same parameters were compared with respect to age, the serum P level of subgroup A in cows with RP was determined to be lower than that of subgroup B and C of the same group and all subgroups of group 2 (Pless than or equal to0.05). Although the serum levels of Ca, P and AP of group 1 were lower than those of group 2, the variation was not statistically significant. However, as the etiology of the retained placenta is very broad, the lower serum level of the parameters analyzed may have some effects on the RP.
Retensiyo sekundinarumlu ineklerde kan serumu kalsiyum (Ca), fosfor (P) ve alkaline phosphatase (AP) düzeyleri üzerine çalişma
Keywords: retained placenta; serum; Ca; P; AP; cow